PERAN MAHASISWA DALAM PENGEMBANGAN DESTINASI WISATA LOKAL YANG BERKELANJUTAN - Mohamad Akasah (Paradigma Mandiri : Jurnal Pengabdian Kepada Masyarakat, 2025)
Student involvement in implementing student work lectures (KKM) Stisip Widyapuri Mandiri Sukabumi, is a development of the tri dharma of higher education which is oriented towards learning and developing knowledge that will be owned by students, the implementation of this KKM aims for KKM participants to become independent and skilled in the community. The purpose of students who carry out this KKM is to open access to tourism in Gunungsungging Village, Surade District, Sukabumi Regency so that it can increase regional income in the village, the development of existing tourism is the existence of the Megadon Museum site. The existence of the Megadon Museum is one of the tourist attractions that can be developed considering the value of science by facilitating access to tourist attractions that are recommended to continue to be developed.